Mother Tongue as a Seasonal Map: Educating Time at Sea Through the Mandar Language Lexicon - Suparman, Suparman; Gunawan, Hendra (JUPE : Jurnal Pendidikan Mandala, 2025)
This research investigates the role of the Mandar language as a seasonal framework that conveys knowledge about maritime time, utilizing an ecolinguistic perspective that encompasses biological, sociological, and ideological aspects. Through in-depth interviews with traditional fishermen from Gili Tapan, Labuhan Sangoro Village, and Ngali Island, combined with documentation of local terms linked to seasons and wind directions, the study reveals that the Mandar lexicon captures extensive ecological knowledge. Key terms like Anging Bara, Anging Timor and Tasi Mare not only describe environmental conditions but also aid in navigation, preserve cultural heritage, and reflect spiritual beliefs. From a biological standpoint, language reveals adaptive strategies aligned with natural cycles, influencing fishing practices and safety. Sociologically, it facilitates the transmission of knowledge across generations, particularly among coastal youth. Ideologically, the Mandar language conveys ecological respect through taboos and phrases that promote harmony with the environment. These linguistic expressions are crucial for maintaining cultural identity and social cohesion while supporting sustainable marine management. wisdom into contemporary sustainability efforts. Ultimately, the findings affirm that language Furthermore, they act as ecological indicators that enhance community resilience in the face of climate change and environmental challenges.